Base-Promoted Tandem Cyclization for the Synthesis of Polyfunctional 2-Hydroxy-2,3-dihydrofurans from Arylglyoxal Monohydrates and 3-(1H-Indol-3-yl)-3-oxopropanenitrile - Cai, Qun; Sheng, Hui-Yang; Li, Deng-Kui; Liu, Yi; Wu, An-Xin (Synlett, 2018)
An efficient base-promoted tandem cyclization for the synthesis of polyfunctional 2-hydroxy-2,3-dihydrofurans from arylglyoxal monohydrates and 3-(1H-indol-3-yl)-3-oxopropanenitrile has been established. The investigation of the mechanism suggested that this reaction proceeds through a Knoevenagel condensation–Michael addition–oxidation–cyclization sequence. This method demonstrates the compatibility with a wide range of functional groups to produce the 2-hydroxy-2,3-dihydrofuran scaffolds in good to excellent yields in one pot.
Keywords: 2-hydroxy-2,3-dihydrofurans; tandem cyclization; arylglyoxal monohydrates; 3-(1H-indol-3-yl)-3-oxopropanenitrile; one pot